Working mothers and their multivoiced self (2012)
Since the 1960's, work has been a goal for Brazilian middle class women. In contrast, mothers of lower-income groups have always needed to work. This qualitative study investigated the meaning of motherhood, child care and work among 28 working mothers of different social classes. In order to do so, interviews and focus groups were conducted. Results show that women attribute exclusively to mothers the child care function. In addition, being a working woman has different meanings for each of those two social classes. There are voices in the self that represent the positions of mother and worker. They act on the meaning systems and they can lead to contradictory attitudes in a similar context.